The Effect of Type-II Collagen on Y-Balance Performance in Men With Meniscus - Taşkın, Cengiz; TAŞKIN, Ali Kemal; YILMAZ, Mehmet; DELİHACIOĞLU, Cevdet Can and TÜMKAYA, Ümmühan and YAMAKOĞLU, Ercan (Progress in Nutrition, 2022)
In the present study, the effect of hydrolyzed type-II collagen supplementation on Y balance performance was examined within the individuals that have second-degree meniscus damage. 10 experiments with an average age of 46.9 ± 3.61 and 10 control groups with an average age of 47.4 ± 2.12 took part in this study, including 20 male patients in total. Throughout the study, the experimental group patients received hydrolyzed type-II collagen treatment orally on an empty stomach for 10 g/days in the morning for three months. On the other hand, the control group patients did not receive any additional nutritional supplements. As a result of the statistical analysis that is made at the end of the study, there are significant differences that are determined within the Y balance test pre-test and post-test performance values of the experimental group (p <0.05). There were no significant differences in the pre-test and post-test performance values of the control group (p> 0.05). As a result, it can be said that collagen type-II supplementation, which is produced by the cartilage matrix in the body and is very important in terms of joint health and cartilage formation, has positive effects on the balance performance of individuals with meniscus damage. Consequently, it can be said that collagen type-II supplementation, which is produced by the cartilage matrix in the body and that is critical in terms of joint health and cartilage formation, has positive effects on the balance performance of individuals with meniscus damage.